Estudo de caso sobre gestão da qualidade em uma empresa de serviços de telefonia fixa. - Ricci, Marlucy Godoy (2003)
The privatization of Telebras opened the national telephone market to competition,strengthening the importance of employing a management program having quality as a competitive advantage. Quality management as competitive strategy is an innovation in a sector that is no longer characterized by a monopoly market structure without competition. This study aims mainly at presenting the current quality management of a fixed line phone company. In this study, organizational structure for quality, a quality management program used by the studied company, methodologies and tools utilized, indicators of quality performance and improvement actions are presented and analyzed. A case study methodology was used. From the case study it can be concluded that in a telephone company quality management is directed at enhancing its competitive capacity the way it occurs in markets that face tough competition. The quality of fixed line phone service is differentiated depending on the kind of consumers, who are classified according to the amount of service utilized, since it is a private company, and therefore, seeks profit. In general, quality goals demanded by The National Telecommunications Agency have been met by the company, which confirms some foreseen trends after the privatization of the sector, at least in the area the company serves.